From "Queue Jumpers" to "Absolute Scum of the Earth": Refugee and Organised Criminal Deviance in Australian Asylum Policy. (5th June 2013) - Cameron, Matthew
<x xml:space="preserve">Abstract</x> The arrival of asylum seekers by boat in Australia is no longer represented as a threat by the Australian government because of characteristics of asylum seekers themselves, but is instead predominantly represented as threatening because of the involvement of transnational organised crime in the form of people smugglers. This progression, which is demonstrated by comparison of the approach of the Howard coalition government with that of the Rudd and Gillard Labor governments, is best understood by reference to conventional understandings of organised crime and irregular migration, and critical accounts of both phenomena. Understood in this way, organised crime and people‐smuggling discourses serve to externalise the asylum seeker "problem" and maintain punitive policies, inhibiting the development of effective regional responses to the issue.